2018
DOI: 10.1371/journal.pone.0204885
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perceived needs for medical services for non-specific low back pain: A systematic scoping review

Abstract: BackgroundAn improved understanding of patients’ perceived needs for medical services for low back pain (LBP) will enable healthcare providers to better align service provision with patient expectations, thus improving patient and health care system outcomes. Thus, we aimed to identify the existing literature regarding patients’ perceived needs for medical services for LBP.MethodsA systematic scoping review was performed of publications identified from MEDLINE, EMBASE, CINAHL and PsycINFO (1990–2016). Descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 115 publications
(345 reference statements)
4
46
0
3
Order By: Relevance
“…A vast majority (88%) consider MR scans important for their recovery. A scoping review of patients' needs for medical services found that the preference for spinal imaging was driven by their desire for a diagnosis but also by the need for the legitimisation of their symptoms [35].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…A vast majority (88%) consider MR scans important for their recovery. A scoping review of patients' needs for medical services found that the preference for spinal imaging was driven by their desire for a diagnosis but also by the need for the legitimisation of their symptoms [35].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Each review targeted various health conditions and populations such as non-specific low back pain [ 19 , 20 , 23 , 36 , 37 , 41 , 44 , 47 , 49 , 50 , 52 ] ( n = 11 reviews, n = 37,408 participants), osteoporosis [ 21 , 39 , 45 ] ( n = 3 reviews, n = 17,534 participants), osteoarthritis [ 22 , 25 , 40 ] ( n = 3 reviews, n = 3157 participants), rheumatoid arthritis [ 26 , 38 , 42 , 43 ] ( n = 4 reviews, n = 9406 participants), and other musculoskeletal disorders (e.g., chronic pain, soft tissue injuries, lower-limb sports-related injuries, traumatic musculoskeletal injuries, mixed and unspecified) [ 10 , 24 , 46 , 48 , 51 , 53 – 56 ] ( n = 9 reviews, n = 61,772 participants) that sought unspecified physical therapy services or rehabilitative cares. Table 2 provides an overview of the characteristics of the included reviews.…”
Section: Resultsmentioning
confidence: 99%
“…All of the reviews specified their population of interest and main outcome (question 1) and all listed their databases, keywords, and inclusion/exclusion criterion in their search strategies (questions 2 and 4). Eighteen (60%) out of the 28 reviews [ 19 22 , 25 , 36 , 38 , 41 , 43 , 44 , 46 49 , 52 , 53 , 55 , 56 ] involved at least two reviewers independently performed study selection (question 5) and eighteen (60%) of them [ 20 22 , 25 , 36 , 38 , 41 43 , 45 51 , 53 , 56 ] involved at least two reviewers independently performing data extraction and reaching consensus (question 6). For question 8, most of the reviews ( n = 27, 90%) [ 10 , 19 22 , 24 26 , 36 , 39 56 ] described and organized their included studies in adequate detail, providing information such as population, outcomes, research designs, and study settings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for radiology imaging in the present study are unknown. Perhaps patients with on-going WAD continue to search for a diagnosis to legitimise their pain, and may request or demand additional testing [33,34]. Clinicians may not be adequately prepared to explain reasons why imaging may be inappropriate and possibly detrimental [35], or may fear missing a fracture [32].…”
Section: Discussionmentioning
confidence: 99%